Production Performance and Nitrogen and Phosphorus Mass Balance in Biofloc-based African Catfish Intensive Culture at Different Densities - Sumitro; Budiardi, Tatag; Fauzi, Hilmi; Ekasari, Julie (Indonesian Society of Scientific Aquaculture (ISSA), 2021)
This study aimed to evaluate the production performance and nitrogen and phosphorus mass balance of biofloc-based intensive African catfish Clarias gariepinus culture at different densities. African catfish with an average body weight of 2.64 ± 0.06 g was randomly distributed into 12 units of round tank with a working volume of 2 m3 of water and maintained for 8 weeks. A completely randomized experimental design with four treatments (in triplicates), i.e. a control treatment at a fish density of 500 fish m-3 with regular water exchange and without organic carbon source addition, and biofloc treatments (BFT) at three different densities, i.e. 500 fish m-3 (BFT500), 750 fish m-3 (BFT750), and 1000 fish m-3 (BFT1000). Biofloc systems were performed with a regular addition of tapioca flour (40% C). The production performance between biofloc system and the control was not significantly different, however water and nitrogen utilizations were significantly more efficient in biofloc system than those of the control. The highest fish specific growth rate was observed in BFT1000 and BFT500 (6.01% day-1 and 5.96% day-1, respectively) (P<0.05). Fish density significantly affected the fish growth performance and productivity in biofloc systems, but not nitrogen and phosphorus utilizations. In conclusion, higher fish density significantly increased the production and water utilization efficiency in biofloc systems, but has no effect on nitrogen and phosphorus utilization efficiency. Furthermore, increasing the fish density could significantly reduce the fish survival and require more efforts to control biofloc biomass in the culture system.